Modelo ProLab: NEURALVISIO minero plataforma de asistencia remota en seguridad y eficiencia con integración de realidad aumentada y redes neuronales - Apolinario Villafan, Ever Panchito (2024)
Neuravisio Minero, an innovative platform that integrates augmented reality and predictive analysis through neural networks, has been designed to reinforce safety and performance in mining operations. The development of this technology responds to the urgent need to reduce emergencies and accidents in mining work, which threaten the quality of life of workers and their own existence, as well as business productivity. This report provides a comprehensive assessment of the technical, financial and social feasibility of Neuravisio Minero, based on market research, usability testing and financial analysis. Its purpose is to inform stakeholders and potential investors about the benefits and return on investment offered by the implementation of this technological provision in the mining industry. Interviews with workers and operations managers have revealed a high demand for advanced accident prevention solutions. Studies indicate that 90% of technicians and engineers prefer Neuravisio Minero over traditional methods due to its effectiveness in preventing accidents, highlighting a potential increase of 30% in operational efficiency and a reduction of up to 50% in time. of inactivity. Usability tests have confirmed the effectiveness of Neuravisio Minero, with 85% of participants reporting significant improvements in the execution of security tasks. The financial Net Present Value (NPV) is calculated at 4,171,440.91 Soles, with a Present Value (PV) of the projected cash flows of 5,145,454 Soles, exceeding the initial investment of S/974,013.33 Soles and demonstrating the profitability of the investment. Furthermore, the calculated Social NPV of 30,169,615.79 Soles reflects the long-term social benefit, highlighting the viability and social profitability of the project.